Penilaian Ciri-Ciri Afektif Dalam Sistem Kurikulum Bersepadu Sekolah Menengah - Satu Pandangan - Ismail, Mokhtar (Penerbit Universiti Sains Malaysia, 1989)
One of the most significant changes in the history of our curriculum development is the introduction of the KBSR and KBSM to our educational system. The prim.e objective of the KBSM system is to produce future schoolleavers who are emotionally, intelectually, and physically balanced. In this respect, 'values' viz 'nilai-nilai murni' are formally taught in schools as a part of every school subject.